An investigation into the perceived effects of a school management/leadership training programme in the Ondangwa East Education Region of Namibia - Udjombala, Josia S (Rhodes University, Faculty of Education, Department of Education, 2007)
The study set out to investigate the perceived effects of the Leadership Development Programme, a two-years training programme for school principals in the Ondangwa East Educational Region of Namibia. The objective has been to find out whether the training curriculum and content were related to what participating principals thought they needed to help them to do their work better, and improve their schools. Data were collected through interviews with two of the first group of nine principals who have completed the training. The study has found that the Leadership Development Programme helped the participating principals to experience personal changes and professional growth. Through the process of participatory action research, the Leadership Development Programme has been able to bring together theory and practice. It has also helped the principals to recognize their responsibility for planning, implementing and evaluation of action, and problem solving initiatives in their schools. The study has also found that the Leadership Development Programme recognized, and therefore applied, the element of experiential/adult learning. Although the Programme has had its basic core curriculum, its content and training process have been flexible in the sense that the Programme tried first to establish what participants knew, and then assisted them to gain a new and enquiring perspective on their knowledge and practice, which helped them to become reflective practitioners. While the study could not establish with a degree of certainty as to what extent the principals have taken up the processes of the training Programme in their schools, it has, however, found that there are many positive changes brought in about schools during the time the training was running. Secondly, while the study could obviously not establish a direct link between every change and the inputs made by the training Programme, it concluded, however, that the Programme at least brought about changes in the mindsets of principals, which were conducive to teaching and learning. What was important, though, was the question of how many of the initiatives were still bearing fruit three years after the training has taken place.
Keywords: Educational leadership -- Namibia -- Ondangwa; School principals -- Namibia -- Ondangwa; School management and organization -- Namibia -- Ondangwa; School principals -- Training of -- Namibia -- Ondangwa; School improvement programs -- Namibia -- Ondangwa; Action research in education